Evolutionary aspects of lipoxygenases and genetic diversity of human leukotriene signaling. (January 2015) - Horn, Thomas; Adel, Susan; Schumann, Ralf; Sur, Saubashya; Kakularam, Kumar Reddy; Polamarasetty, Aparoy; Redanna, Pallu; Kuhn, Hartmut; Heydeck, Dagmar
Abstract: Leukotrienes are pro-inflammatory lipid mediators, which are biosynthesized via the lipoxygenase pathway of the arachidonic acid cascade. Lipoxygenases form a family of lipid peroxidizing enzymes and human lipoxygenase isoforms have been implicated in the pathogenesis of inflammatory, hyperproliferative (cancer) and neurodegenerative diseases. Lipoxygenases are not restricted to humans but also occur in a large number of pro- and eucaryotic organisms. Lipoxygenase-like sequences have been identified in the three domains of life (bacteria, archaea, eucarya) but because of lacking functional data the occurrence of catalytically active lipoxygenases in archaea still remains an open question. Although the physiological and/or pathophysiological functions of various lipoxygenase isoforms have been studied throughout the last three decades there is no unifying concept for the biological importance of these enzymes. In this review we are summarizing the current knowledge on the distribution of lipoxygenases in living single and multicellular organisms with particular emphasis to higher vertebrates and will also focus on the genetic diversity of enzymes and receptors involved in human leukotriene signaling.